The Nursing Division of the Israeli Health Ministry Moves Nursing Into the Forefront of Health Care. (February 2014) - Greenberger, Chaya; Haron, Yafa; Riba, Shoshana
The Nursing Division of the Israeli Ministry of Health, with the Government Nursing Officer at its helm, plays a pivotal role in promoting the nursing profession and influencing national health policy. In terms of nursing, the division is authorized to set, upgrade, and audit professional standards; create new specialties; formulate, oversee, and accredit educational programs; and award license to practice. In terms of broad policy, it has a voice in shaping general health priorities and allocating resources. Through the strategic use of the Nursing Division's vested powers and in collaboration and consultation with stakeholders, current nursing roles are being expanded and new ones are being developed to meet the needs of the population. The aim of this article is to describe and analyze the contribution of the Nursing Division under leadership of the Government Nursing Officer in promoting nursing and health care in Israel over the last decade.